The profiling and analysis of gene expression in human periodontal ligament tissue and fibroblasts - Nattakarn Hosiriluck; Haruna Kashio; Ayuko Takada; Itaru Mizuguchi; Toshiya Arakawa (Wiley, 2022)
Abstract Objectives The periodontal ligament (PDL) is an important component of periodontium to support dental structure in the alveolar socket. Regeneration of PDL tissue is an effective treatment option for periodontal disease and the profiling of genes involved in this process will be informative. Therefore, our study aims to accurately delineate the profiling of gene expression for PDL tissue regeneration. Materials and Methods We isolated PDL tissues and PDL fibroblasts (PDLFs) from premolar teeth, which were extracted from healthy periodontal status patients undergoing orthodontic treatment. Messenger RNA (mRNA) expression in PDL tissue and PDLFs were analyzed using Cap analysis gene expression, which is a second‐generation sequencing technique to create profiling. We also determined the protein expression using Western blot. Results Collagens (type I, III, and VI), noncollagenous proteins (periostin and osteonectin), and proteoglycans (asporin, lumican, decorin, and osteomodulin) were highly expressed in PDL tissue. Integrin, β1 was also expressed in PDL tissue. On comparison of gene expression between PDL tissue and PDLFs, four PDL marker genes, osteopontin, asporin, periostin, and osteonectin, were decreased in PDLFs. The genes for gene regulation were also highly expressed. Conclusions Our study demonstrated the overall profiling of mRNA expression in PDL tissue and analyzed the important genes which may be useful for providing specific information for the reconstruction of PDL. We also identified the difference in gene expression between PDL tissue and PDLFs which might provide insights towards PDL regeneration.